Effects of varying blood flow rate during peripheral veno-arterial extracorporeal membrane oxygen (V-A ECMO) on left ventricular function measured by two-dimensional strain - Ng, Pauline Yeung; Ma, Tammy Sin Kwan; Ip, April; Fang, Shu; Li, Andy Chak Cheung; Wong, Alfred Sai Kuen; Ngai, Chun Wai; Chan, Wai Ming; Sin, Wai Ching (Frontiers in Cardiovascular Medicine, 2023)
Background We evaluated the effects of varying blood flow rate during peripheral veno-arterial extracorporeal membrane oxygen (V-A ECMO) on left ventricular function measured by two-dimensional strain. Methods Adult patients who were supported by peripheral V-A ECMO were recruited. Serial hemodynamic and cardiac performance parameters were measured by transthoracic echocardiogram within the first 48 hours after implementation of V-A ECMO. Measurements at 100%, 120%, and 50% of target blood flow (TBF) were compared. Results A total of 54 patients were included and the main indications for V-A ECMO were myocardial infarction [32 (59.3%)] and myocarditis [6 (11.1%)]. With extracorporeal blood flow at 50% compared with 100% TBF, the mean arterial pressure was lower [66±19 vs 75±18 mmHg, p<0.001], stroke volume was greater [23 (12-34) vs 15 (8-26) mL, p<0.001], and cardiac index was higher [1.2 (0.7-1.7) vs 0.8 (0.5-1.3) L/min/m2, p<0.001]. Left ventricular contractile function measured by global longitudinal strain improved at 50% compared with 100% TBF [-2.8 (-7.6- -0.1) vs -1.2 (-5.2-0) %, p<0.001]. Similarly, left ventricular ejection fraction increased [24.4 (15.8-35.5) vs 16.7 (10.0-28.5) %, p<0.001] and left ventricular outflow tract velocity time integral increased [7.7 (3.8-11.4) vs 4.8 (2.5-8.5) cm, p<0.001]. Adding echocardiographic parameters of LV systolic function to the Survival After Veno-arterial ECMO (SAVE) score had better discriminatory value in predicting eventual hospital mortality (AUROC 0.69, 95% CI 0.55-0.84, p=0.008) and successful weaning from V-A ECMO (AUROC 0.68, 95% CI 0.53-0.83, p=0.017). Conclusion In the initial period of V-A ECMO support, measures of left ventricular function including LVEF and global longitudinal strain were inversely related to ECMO blood flow rate. Understanding the heart-ECMO interaction is vital to interpretation of echocardiographic measures of the left ventricle while on ECMO.